2014
DOI: 10.4103/0976-9668.127293
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implants in anterior maxillary arch

Abstract: Aim:The aim of the study was to evaluate the osseo-integration and soft tissue status of the endosseous implants placed in immediate extraction socket.Methodology:Seven patients (4 males and 3 females) aged 20-30 years were selected for the study. Nine implants were placed in seven patients in the maxillary arch. All the patients were clinically αnd thoroughly examined. Under local anesthesia, the indicated tooth was extracted. The extracted socket was prepared using standard drills with palatal wall as guide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In the study, the mean IS at T 0 was 63.67 and 63.87 in the groups A and B, respectively. This was satisfactory according to previous reports of Shiigai et al [13] and Anitha et al [14], who stated that the primary implant stability with ISQ above 62 was considered suitable; however, Lai et al observed a mean ISQ of 68.0 with RBH of 48 mm [15].…”
Section: Discussionsupporting
confidence: 66%
“…In the study, the mean IS at T 0 was 63.67 and 63.87 in the groups A and B, respectively. This was satisfactory according to previous reports of Shiigai et al [13] and Anitha et al [14], who stated that the primary implant stability with ISQ above 62 was considered suitable; however, Lai et al observed a mean ISQ of 68.0 with RBH of 48 mm [15].…”
Section: Discussionsupporting
confidence: 66%
“…[ 20 ] Anitha et al . [ 21 ] stated that the distance from the implant shoulder to crest of alveolar bone at base line initially was 0.3 ± 0.3 mm and at the 6 th month follow up, increased to 0.5 ± 0.5 mm. Whereas, Pal et al .…”
Section: Discussionmentioning
confidence: 99%
“…Dental implants are nowadays considered the most acceptable treatment for replacing missing teeth. 1 - 3 Placement of dental implants in the anterior maxilla may sometimes have some limitations from the depth and angulation aspects due to anatomical landmarks, esthetic considerations, and possible bone loss following tooth extraction. 4 , 5 The nasal cavity, maxillary sinus, and nasopalatine duct are among landmarks of great importance and may even put implant surgical preparation at risk.…”
Section: Introductionmentioning
confidence: 99%